Mortality of veteran participants in the Crossroads nuclear test - Johnson, J. Christopher (National Academy Press, 1996)
In 1946, approximately 40,000 U.S. military personnel participated in Operation CROSSROADS, an atmospheric nuclear test that took place at Bikini Atoll in the Marshall Islands. Congress passed a law directing the Veterans Administration to determine whether there were any long-term adverse health effects associated with exposure to ionizing radiation from the detonation of nuclear devices. This book contains the results of an extensive epidemiological study of the mortality of participants compared with a similar group of nonparticipants. Topics of discussion include a breakdown of the study rationale; an overview of other studies of veteran participants in nuclear tests; and descriptions of Operation CROSSROADS, data sources for the study, participant and comparison cohorts, exposure details, mortality ascertainment, and findings and conclusions.